EFEKTIVITAS PERAN BPSK DALAM PENYELESAIAN SENGKETA KONSUMEN DITINJAU DARI DAYA IKAT PUTUSAN - Sri Agustini; Miasiratni Miasiratni (Ensiklopedia of Journal, 2026)
The Consumer Dispute Settlement Agency (BPSK) was established as an alternative dispute resolution body between consumers and business actors that emphasizes efficiency, simplicity, and low cost. Law Number 8 of 1999 on Consumer Protection stipulates that BPSK decisions are final and binding. However, in practice, the binding force and enforcement of BPSK decisions still encounter significant obstacles, particularly due to the possibility of filing objections before the District Court and the absence of independent executorial power. This study aims to analyze the effectiveness of BPSK’s role in resolving consumer disputes by focusing on the binding force and implementation of its decisions. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that although BPSK decisions are normatively declared final and binding, their practical effectiveness remains limited and has not fully ensured legal certainty for consumers. Therefore, strengthening the regulatory framework and enforcement mechanisms is necessary to enhance the effectiveness of BPSK in providing legal protection for consumers.Keywords: BPSK, Consumer Protection, Decisions